First report of Colletotrichum fructicola causing anthracnose on Pouteria campechiana in China - Yang, Zhini (Plant disease, 2020)
Pouteria campechiana (Kunth) Baehni (=Lucuma nervosa A. DC.) is a fruit crop planted in southern China (Gao et al. 2019). It is originally from Central America, and also grown there commercially as well as in some American states (Fadzilah et al. 2018). In March 2019, a leaf spot disease was found on P. campechiana in Baoshan, Yunnan, China. Field surveys were done in a 0.06 ha orchard in Yunnan Province. Leaf spots were found on 90% of six-year-old plants in this field and were observed in other planting areas. The symptoms initially appeared as small, round, brown spots. As the disease developed, the center of the lesions was sunken with a dark brown border (Fig. 1). Under severe conditions, some spots were joined into larger irregular spots, and even whole leaves died. The disease severity of different plants varied, and some leaves showed only a few brown spots while others showed many spots. Small fragments of diseased tissues (3×3 mm) were disinfected in 75% ethanol for 10 s, 1% NaClO for 1 min, and rinsed three times in sterilized water. Then, tissues were placed onto potato dextrose agar (PDA), and incubated at 25°C in the dark for 5 days. Fungal isolates with similar morphology were consistently recovered from diseased tissues. The 25 colonies were initially cottony, pale white to pale gray on the upper side and greyish-green with black zonation on the underside of plates. Conidia were single-celled and hyaline, aseptate, straight, and cylindrical, with rounded ends (Fig. 1B). The length and width of 200 conidia were measured for two representative isolates, DHG-1 and DHG-2, and these averaged 14.48 × 5.59 μm and 14.92 × 5.57 μm. Appressoria were ovoid, sometimes clavate, brown, averaged 7.47 × 5.86 μm and 7.25 × 5.85 μm (n=30). Brown and globose ascocarp were observed on the leaves of Pouteria campechiana. Asci were unitunicate, thin-walled, 6-8 spored, clavate, averaged 51.53×13.01 μm and 50.21 × 13.32 μm (n=30). Ascospores were hyaline, one-celled, slightly curved to curved with obtuse to slightly rounded ends, averaged 14.64×5.97 μm and 15.19 × 6.23 μm (n=30). These two isolates were selected for molecular identification. DNA was extracted from mycelia with the DNA secure Plant Kit (TIANGEN, Biotech, China). For further molecular identification, the internal transcribed spacer (ITS), partial actin (ACT), calmodulin (CAL), chitin synthase (CHS-1), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), beta-tubulin (TUB2), and the Apn2-Mat1-2 intergenic spacer and partial mating type (Mat1-2) gene (ApMat) genes of the strains (DHG-1, DHG-2) were amplified using the primer pairs ITS1/ITS4, ACT-512F/ACT-783R, CL1C/CL2C, CHS-79F/CHS-345R, GDF1/GDR1, T1/Bt-2b, and AM-F/AM-R (Weir et al. 2012; Silva et al. 2012), respectively.The sequences were obtained and compared with GenBank and they all showed over 99% identity to the type strain of Colletotrichum fructicola ICMP 18581 (Accession nos. JX010165, JX010033, JQ807838, FJ907426, JX010405, JX009866, and FJ917508) (Weir et al. 2012). A phylogenetic tree based on the combined ITS, ACT, CAL, CHS-1, TUB2, GAPDH and ApMat sequences using the Neighbor-joining algorithm revealed that the isolates were C. fructicola (Fig. 2). The sequences were deposited into GenBank with accession MN955541, MN955542, and MN966581 to MN966592. Pathogenicity tests were conducted on eighteen healthy and tender leaves of six 1-year-old P. campechiana plants in a greenhouse. The experiment was repeated twice. The length and width of the inoculated leaves were between 8-13 cm × 2.5-3.6 cm. The epidermis of each tested leaf was lightly scratched in six separate areas with a sterilized needle. Each isolate was inoculated onto at least three wounded leaves by placing 20 μL of a conidial suspension (106 conidia/mL) on the wound sites. Control leaves were also wounded and inoculated with distilled water. All the plants were then sprayed with distilled water and covered with plastic bags. After 10 days, initial symptoms appeared as circular and deep yellow spots. After a few more days, the spots became brown, enlarged to up to 4.0 mm which was similar to symptoms observed in the field, whereas controls remained symptomless. Koch's postulates were fulfilled by re-isolation of C. fructicola from diseased leaves, and identification confirmed by sequencing. Colletotrichum fructicola has been associated with anthracnose on mango, apple, pear and cassava (Oliveira et al. 2018). To our knowledge, this is the first report of C. fructicola associated with anthracnose of P. campechiana worldwide. These results will provide crucial information for future epidemiological studies and for management of this disease